Specific miRNAs are associated with human cancer cachexia in an organ‐specific manner - Tanja Krauss; Simone Heisz; Julius Honecker; Olga Prokopchuk; Marc Martignoni; Klaus‐Peter Janssen; Melina Claussnitzer; Hans Hauner; Claudine Seeliger (Wiley, 2023)
Abstract Background Cancer cachexia (CCx) is a complex and multi‐organ wasting syndrome characterized by substantial weight loss and poor prognosis. An improved understanding of the mechanisms involved in the onset and progression of cancer cachexia is essential. How microRNAs contribute to the clinical manifestation and progression of CCx remains elusive. The aim of this study was to identify specific miRNAs related to organ‐specific CCx and explore their functional role in humans. Methods miRNA patterns in serum and in cachexia target organs (liver, muscle and adipose tissue) from weight stable (N ≤ 12) and cachectic patients (N ≤ 23) with gastrointestinal cancer were analysed. As a first step, a miRNA array (158 miRNAs) was performed in pooled serum samples. Identified miRNAs were validated in serum and corresponding tissue samples. Using in silico prediction, related genes were identified and evaluated. The findings were confirmed in vitro by siRNA knock‐down experiments in human visceral preadipocytes and C2C12 myoblast cells and consecutive gene expression analyses. Results Validating the results of the array, a 2‐fold down‐regulation of miR‐122‐5p (P = 0.0396) and a 4.5‐fold down‐regulation of miR‐194‐5p (P < 0.0001) in serum of CCx patients in comparison with healthy controls were detected. Only miR‐122‐5p correlated with weight loss and CCx status (P = 0.0367). Analysing corresponding tissues six muscle and eight visceral adipose tissue (VAT) cachexia‐associated miRNAs were identified. miR‐27b‐3p, miR‐375 and miR‐424‐5p were the most consistently affected miRNAs in tissues of CCx patients correlating negatively with the severity of body weight loss (P = 0.0386, P = 0.0112 and P = 0.0075, respectively). We identified numerous putative target genes of the miRNAs in association with muscle atrophy and lipolysis pathways. Knock‐down experiments in C2C12 myoblast cells revealed an association of miR‐27b‐3p and the in silico predicted atrophy‐related target genes IL‐15 and TRIM63. Both were up‐regulated in miR‐27b‐3p knock‐down cells (P < 0.05). Concordantly, in muscle tissue of CCx individuals, significant higher expression levels of IL‐15 (P = 0.0237) and TRIM63 (P = 0.0442) were detected. miR‐424‐5p was identified to regulate the expression of lipase genes. Knock‐down experiments in human visceral preadipocytes revealed an inverse association of miR‐424‐5p with its predicted target genes LIPE, PNPLA2, MGLL and LPL (P < 0.01). Conclusions The identified miRNAs, in particular miR‐122‐5p, miR‐27b‐3p, miR‐375 and miR‐424‐5p, represent features of human CCx and may contribute to tissue wasting and skeletal muscle atrophy through the regulation of catabolic signals. Further studies are needed to explore the potential of the identified miRNAs as a screening tool for early detection of cancer cachexia.